Ground Deformation during Papandayan Volcano 2002 Eruption as Detected by GPS Surveys - Abidin, Hasanuddin Z.; Andreas, H.; Gamal, M.; Sugandar, Ony K.; Meilano, Irwan; Hendrasto, M.; Kusuma, M. A.; Darmawan, D.; Purbawinata, M. A.; Wirakusumah, A. D.; Kimata, F. (Journal of Engineering and Technological Sciences, 2003)
Papandayan is an A-type active volcano located in the southern part of Garut Regency, about 70 km southeast of Bandung, Indonesia. Its earliest recorded eruption, and most violent and devastating outburst occurred in 1772 and the latest eruptions occurred in the period of 11 November to 8 December 2002, and consisted of freatic, freatomagmatic and magmatic types of eruption.During the latest eruption period, GPS surveys were conducted at several points inside and around the crater in a radial mode using the reference point located at Papandayan observatory around 10 km from the crater. At the points closest to the erupting craters, GPS displacements up to a few dm were detected, whereas at the points outside the crater, the displacements were in the cm level. The magnitude of displacements observed at each point also show a temporal variation according to the eruption characteristics. The results show that deformation during eruption tends to be local, e.g. just around the crater. Pressure source is difficult to be properly modeled from GPS results, due to limited GPS data available and differences in topography, geological structure and/or rheology related to each GPS station.